2013
DOI: 10.1038/emboj.2013.164
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cell cycle control during oocyte-to-embryo transitions

Abstract: Ex ovo omnia-all animals come from eggs-this statement made in 1651 by the English physician William Harvey marks a seminal break with the doctrine that all essential characteristics of offspring are contributed by their fathers, while mothers contribute only a material substrate. More than 360 years later, we now have a comprehensive understanding of how haploid gametes are generated during meiosis to allow the formation of diploid offspring when sperm and egg cells fuse. In most species, immature oocytes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 144 publications
0
31
0
6
Order By: Relevance
“…The goal of meiosis is to generate haploid gametes, allowing for the formation of diploid offspring upon fertilization [47]. Meiosis involves two rounds of cell division (meiosis I and meiosis II) without an intervening round of DNA replication.…”
Section: O-glcnac In Meiosismentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of meiosis is to generate haploid gametes, allowing for the formation of diploid offspring upon fertilization [47]. Meiosis involves two rounds of cell division (meiosis I and meiosis II) without an intervening round of DNA replication.…”
Section: O-glcnac In Meiosismentioning
confidence: 99%
“…Meiosis involves two rounds of cell division (meiosis I and meiosis II) without an intervening round of DNA replication. In mammals, fully grown oocytes in the ovary are arrested in prophase I, and it is only upon hormonal stimulation at the time of ovulation that they will resume meiosis, progress through meiosis I, and then arrest at metaphase of meiosis II [47]. Then, it is only following fertilization that the second meiotic arrest will be released and zygotes will enter early embryonic mitotic divisions [47].…”
Section: O-glcnac In Meiosismentioning
confidence: 99%
See 1 more Smart Citation
“…Xenopus eggs have been used in studies on egg maturation, egg activation and other mechanisms, which facilitated the progress of developmental biology (1,2). It has been shown that signalling pathways including protein phosphorylation and dephosphorylation participate greatly in these regulation mechanisms (1,3,4).…”
mentioning
confidence: 99%
“…It has been shown that signalling pathways including protein phosphorylation and dephosphorylation participate greatly in these regulation mechanisms (1,3,4). To clarify the complicated regulation mechanism of egg activation, comprehensive analysis of protein phosphorylation during egg activation is a powerful means.…”
mentioning
confidence: 99%